Influence of Surfactants on the Characteristics of Nickel Matrix Nanocomposite Coatings. (3rd February 2013) - Fahami, Abbas; Nasiri-Tabrizi, Bahman; Rostami, Mohsen; Ebrahimi-Kahrizsangi, Reza
Abstract : Nickel-based nanocomposite coatings were prepared from a Watts-type electrolyte containing reinforcement's particles (silicon carbide and graphite) to deposit onto the steel St-37 substrate. The electrochemical plating of the coatings in absence and presence of surfactants and reinforcements particles was carried out to optimize high quality coatings with appropriate mechanical and morphological features. The surfactants such as cetyltrimethylammonium bromide (CTAB), sodyumdodecyl sulfate (SDS), and saccharine affected electrodeposition plating and subsequently changed mechanical characteristics. Based on XRD results, the dominant phases in the absence of surfactants were nickel oxide (NiO), nickel, and silicon carbide (SiC), while the main phases in presence of surfactants were nickel (Ni) and SiC. The hardness of the resultant coatings was found to be from 332 to 593 (Hv) depending on the bath parameter and the reinforcements weight percentage (wt%) in the Ni matrix. Microscopic observations illustrated a cluster-like structure which consisted of some fine sphere particulates with average particle size of 65–150 nm. According to elemental mapping spectra, a homogenous distribution of nickel, silicon, and carbon particles appeared into the nickel matrix coating. Finally, the experimental outcomes demonstrated that the surfactants have significant influence on the composition of coatings, surface morphology, and mechanical properties.